Ensinando engenharia de software online para pessoas em situação de vulnerabilidade social - Lisboa, Anielle Severo (2021)
Software is essential in heterogeneous market environments and the most diverse fields of knowledge. Software development is based on Software Engineering, which is part of the curriculum of the undergraduate course. Software Engineering disciplines cover all aspects of software production. Qualified teaching of Software Engineering is essential for future software engineers to follow software development techniques and processes satisfactorily, such as user specifications, standards, methodologies, validation, and maintenance. Social diversity is characterized by people of different races, ethnicities, religious beliefs, socioeconomic status, language, geographical origin, gender, and sexual orientation. Social vulnerability is related to the socioeconomic status of groups of people with few financial resources, education, housing, and/or access to opportunities for their development as a citizen. People in social vulnerability situations have limited access to education and courses to build a profession. In 2020, the COVID-19 Pandemic is affecting the progress of on-site work, classes, and activities. As a result, most educational institutions and companies choose to continue working with remote activities. In this research, we understand how Software Engineering teaching is conducted to people in social vulnerability conditions during the Pandemic. We executed two systematic mappings of the literature: the first one to study diversity in Software Engineering (secondary study) and the second one for teaching in Software Engineering (tertiary study). In the qualitative study, we use semi-structured interview techniques to collect and analyze Grounded Theory methodologies. The main contribution of our research is a set of teaching practices in software engineering in times of Pandemic for people in social vulnerability situations.